Product focused software process improvement 4th international conference, PROFES 2002, Rovaniemi, Finland, December 9-11, 2002 : proceedings / Markku Oivo, Seija Komi-Sirviö (eds.) - Oivo, Markku; Komi-Sirviö, Seija, 1966- (Lecture notes in computer science, 2002)
This book constitutes the refereed proceedings of the 4th International Conference on Product Fucused Software Process Improvement, PROFES 2002, held in Rovaniemi, Finland in December 2002. The 48 revised papers presented together with 2 keynote contributions were carefully reviewed and selected from 70 submissions. The papers are organized in topical sections on improvement management, process modeling, software quality, Agile software development, process improvement approaches, methods and techniques, embedded software process improvement, process improvement case studies, effective use of measurements, wireless services, use cases, knowledge management, embedded systems methods, COTS quality techniques, frameworks, mobile solutions, and methods and techniques.